Health Education Intervention Programs in Early Childhood Education: A Systematic Review - Judit Fináncz; Judit Podráczky; Krisztina Deutsch; Evelin Soós; Henrietta Bánfai-Csonka; Melinda Csima (MDPI AG, 2023)
Adult health behavior is established and formed in childhood, in which, besides the primacy of the family, institutional education plays a significant role. The aim of our systematic review is to analyze health interventions implemented in an institutional environment for children aged 3-6 years. Our research was carried out according to the PRISMA 2020 protocol. The sample of research was determined by using the keywords "health education" or "health promotion" and "preschool" or "kindergarten" in Scopus, ERIC and WOS databases published between 2013 and 2022. Out of a total of 1535 results, 14 proved to be relevant to the eligibility criteria of the study topic. Cochrane Risk of Bias criteria were used for critical appraisal and to limit bias. The majority of the analyzed studies focused on physical activity and nutrition, including the issues of sedentary time, obesity and sustainability. The holistic approach is less typical in the interventions reviewed, with a marginal occurrence of topics related to mental and social health, as well as risk behavior. The interventions proved to be more effective when parents were involved, and the varied, age-appropriate game-based activities also contributed to the formation of health-supporting habits.